Software Quality: Issues, Concerns and New Directions (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Software metrics and quality models have a very important role to play in measurement of software quality. A number of well-known quality models and software metrics are used to build quality software both in industry and in academia. Development of software metrics is an ongoing process with new metrics being continuously tried out.Â  However, during our research on measuring software quality using object oriented design patterns, we faced many issues related to existing software metrics and quality models. For a particular situation of interest, any established metric can be used. If none is found to be appropriate, a new metric can be devised. In this paper, we discuss some of these issues and present our approach to software quality assessment.